Deteccion de las infecciones latentes de Spilocaea oleagina en hojas de olivo - Zarco, A.=700 1 Viruega, J.R.; Roca, L.F.; Trapero, A.
(En, Es)
Ilus., 38 ref.
Keywords: OLEA EUROPAEA; ENFERMEDADES FUNGOSAS; INFECCIONES LATENTES; SPILOCAEA CYCLOCONIUM; CAIDA DE LAS HOJAS; METODOS; HIDROXIDO SODICO; ESPAÑA; REPILO